The Impact of Corporate Social Responsibility Disclosure on Mergers and Acquisitions: A Literature Review of Market Reactions and Long-Term Performance - Benardi Benardi; Ngadi Permana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This literature review examines the impact of Corporate Social Responsibility (CSR) disclosure on mergers and acquisitions (M&A), focusing on market reactions, post-merger integration, and long-term performance. The review reveals that CSR disclosure often leads to positive market reactions, fostering investor confidence and increasing stock prices during M&A announcements. Furthermore, CSR practices contribute to smoother post-merger integration by aligning organizational cultures and fostering trust. Over the long term, companies that integrate CSR into their strategies generally experience enhanced brand value, customer loyalty, and competitive advantage. However, the effectiveness of CSR disclosure depends on its authenticity and strategic alignment with corporate goals. The review also highlights the need for further research in emerging markets and the exploration of qualitative approaches to deepen understanding of CSR’s role in M&A.